Effect of Production Strategy Performance on Brand Royalty - Endrixs Endrianto; Ahmad Zaelani Adnan; Ninin Asmiah; Lia Nurmeliani (PT. Publikasiku Academic Solution, 2022)
Background: Product strategy is a plan that identifies the goals and objectives of a product and then explains the vision to achieve those goals. This helps to relate the vision of the project with the actual methods used to implement it. Product strategy maps out key benchmarks for creating, marketing, and distributing any concept you plan to sell. Aim: The purpose of this study is to determine the effect of production strategy performance on brand royalty in companies and restaurants. Method: The sample used in this study can be determined using the infinite sample formula, with a 95% confidence level and a 10% error level, the sample used in this study was 100 people as respondents. The sampling technique in this study is non probability sampling with the Purposive Sampling. Findings: They also provide a central plan that people across the business can refer to to guide their efforts and fine-tune their overall business strategy. Business in the food sector is a potential business at this time. Factors that need to be considered in facing competition in the restaurant business include products and prices. If these two factors are getting better and more attractive, it can make customers feel satisfied, if customers feel satisfied, they will be loyal to the restaurant